THE EFFECT OF EDUCATIONAL VIDEOS ABOUT REPRODUCTIVE HEALTH ON PROMISCUOUS ATTITUDE IN STUDENTS AT SMP MUHAMMADIYAH 2 GAMPING, SLEMAN, YOGYAKARTA - Nurul Yumna Aisyah; Endang Koni Suryaningsih (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2024)
Background: Teenagers are the next generation who can shape the nation in a better direction and have far-sighted thinking that can benefit themselves, their families, and the surrounding environment. In the same word, teenagers who are still unstable tend to experience lower self-control and self-awareness than adults. Teenagers must understand promiscuity because it can have bad consequences for the growth and development of children as well as teenagers. The study aimed at knowing the effect of educational videos on reproductive health on promiscuous attitude in students at SMP (Junior High School) Muhammadiyah 2 Gamping, Sleman, Yogyakarta.Methods: The research applied the Quasy Experiment with a one-group pretest-posttest design. The population in this study was class VII students amounting to 110 students. The sampling technique used was Proportionate stratified random sampling with a total sample of 43 respondents. The data were analyzed using Paired t-tests.Results: The results of the analysis showed that the average promiscuous attitude before the given intervention was 75.27. The average promiscuous attitude after the given intervention increased to 79.45. With the results of the paired t-test, the p-value of (0.000) ≤ 0.05 was obtained.Conclusion: It can be concluded that educational video about reproductive health influences in improving the promiscuous attitude in students of SMP Muhammadiyah 2 Gamping, Sleman, Yogyakarta.